Implementation Of The Discrete Sine Transform (Dst) Algorithm For Video File Compression - Muhammad Abdillah Nasution; Khairuddin Nasution; Mhd. Zulfansyuri Siambaton (Ilmu Bersama Center, 2026)
Video is one of the multimedia data formats whose use continues to grow across fields such as education, entertainment, and digital communication, a trend that has increased the demand for storage capacity and bandwidth. A video is composed of a large collection of frames containing substantial amounts of pixel data, which results in comparatively large file sizes. This condition calls for a compression method capable of reducing file size without significantly degrading visual quality. This study implements the Discrete Sine Transform (DST) algorithm in the video file compression process and analyzes its effect on file size and video quality. DST is applied to transform data from the spatial domain into the frequency domain so that data redundancy can be reduced while important information is retained. The compression procedure divides each video into a series of frames and applies the DST transformation to optimize data efficiency. Testing was carried out on video files in MP4 and AVI formats, with compressed video quality evaluated using the Peak Signal to Noise Ratio (PSNR) parameter and compression efficiency measured by comparing file sizes before and after compression. The results show that the DST method is able to reduce video file size while maintaining visual quality. The AVI format achieved an average compression efficiency of 44.96%, while the MP4 format achieved 28.76%. In addition, the PSNR values for all tested videos remained above 37 dB, indicating that the compressed video quality can still be classified as good.